Social welfare and severity of criminal punishment - Oleg N. Bibik (Правоприменение, 2019)
The subject. The article is devoted to the correlation between the level of social welfare and the degree of criminal punishment’s repressiveness.The purpose of the article is to confirm or disprove hypothesis that improving the social welfare increases perceiving harmfulness of criminal punishment with its constant formal measure and stimulates the mitigation of criminal sanctions.The methodology of the study includes general scientific methods (analysis, synthesis, de‐ scription) and sociological approach.The main results and scope of their application. The author proves that society is based on reciprocity, the expression of which is the exchange of certain actions between people. The application of criminal punishment in response to the committed crime can be considered as a special case of social exchange that occurs when the crime is committed. Since crime and punishment are included in the process of social exchange, an equivalent is needed to determine their relation. The equivalent in such an exchange is the time of a human's life. Time of human life as an equivalent in social exchange fits perfectly into the logic of development of modern society, culture of consumption. A person's life time is the time when person is able to consume. The reason for the choice of such a value guide is cultural stereotypes. Time is the most important factor in our due to modern cultural values, time plays a decisive role in the formation of the price of crime. The modern system of criminal justice is focused on taking into account the lost time of human life in the application of punishment.Improving the social welfare increases perceiving harmfulness of criminal punishment with its constant formal measure, this process stimulates the mitigation of criminal sanctions. The slowdown in the deflation of criminal punishment for violent crimes is due to a decrease in the social tolerance to violence, which is determined by the development of culture.Conclusions. The general direction of normal development of society is deflation of criminal punishment, its weakening. The change of living standards naturally affects the severity of criminal punishment and is inversely dependent on it – the higher the quality of life, the less the severity of punishment . The practice of deprivation of liberty is an example. The study of the relationship between the use of deprivation of liberty and murder showed that the more economically developed the state, the more the number of murders correlated with the number of persons deprived of liberty. Although murderers are not the dominant group of prisoners, the more murders, the lower the cost of human life in a particular country, the more often deprivation of liberty is used in that country.